User-driven health care: answering multidimensional information needs in individual patients utilizing post?EBM approaches: an operational model - Biswas, Rakesh; Jayanthy Maniam, *; Lee, Edwin Wen Huo; Das, Premalatha Gopal; Shashikiran Umakanth,; Sumit Dahiya,; Sayeed Ahmed, (Blackwell Publishing Ltd, 2008)
The hypothesis in the conceptual model was that a user-driven innovation in presently available information and communication technology infrastructure would be able to meet patient and health professional users information needs and help them attain better health outcomes. An operational model was created to plan a trial on a sample diabetic population utilizing a randomized control trial design, assigning one randomly selected group of diabetics to receive electronic information intervention and analyse if it would improve their health outcomes in comparison with a matched diabetic population who would only receive regular medical intervention. Diabetes was chosen for this particular trial, as it is a major chronic illness in Malaysia as elsewhere in the world. It is in essence a position paper for how the study concept should be organized to stimulate wider discussion prior to beginning the study.